Osteomyelitis of the symphysis pubis after inguinal hernia repair. Reconstruction using anterolateral myocutaneous thigh flap - Moreda Álvarez, Rubén; Darriba Fernández, María I.; Megias Barrera, Joaquim; Trillo Parejo, Pedro; García García, Manuel (Revista Argentina de Cirugía, 2026)
Osteomyelitis of the symphysis pubis is an uncommon condition. Treatment consists of antibiotic therapy, surgical debridement and wound healing by secondary intention. When the defect is large, flaps are necessary for proper healing. We report the case of a male patient who underwent inguinal hernia repair for recurrent hernia using the Linchtenstein technique. Four months later, he visited the emergency room for pain and fever and was diagnosed with osteomyelitis of the symphysis pubis secondary to mesh infection. He was treated with surgical debridement and negative pressure system. Due to the persistence of chronic sinus, reconstruction of the defect was decided using a pedicled anterolateral myocutaneous thigh flap, with favorable outcome. The anterolateral thigh flap has been widely used due to its multiple advantages and low morbidity, as evidenced by the dynamometric studies performed in the postoperative follow-up of these patients.